Immersive walking in a virtual crowd: The effects of the density, speed, and direction of a virtual crowd on human movement behavior. (1st June 2020) - Koilias, Alexandros; Nelson, Michael G.; Anagnostopoulos, Christos‐Nikolaos; Mousas, Christos
Abstract: We investigated the movement behavior of participants walking within a virtual crowd in an immersive virtual environment. We investigated three different parameters that characterize a moving virtual crowd: density, speed, and direction . An immersive road‐crossing scenario that took place in a virtual metropolitan city was created. In this scenario, the participants were instructed to walk toward the opposite sidewalk. Three measurements (speed, deviation, and trajectory length) were used to evaluate the impact of the parameters assigned to the virtual crowd on the movement behavior of the participants. Significant results were found for both the main and interaction effects. The results suggested that the high density, low speed, and diagonal direction situations associated with the virtual crowd had the greatest impacts on the speed, deviation, and trajectory lengths of participants when they walked in a virtual environment and were surrounded by a moving virtual population. Abstract : The parameters of the virtual crowd that were examined in this article. Left: low density (top) versus high density (bottom) situations. Middle: low speed (top) versus high speed (bottom) situations. Right: straight direction (top) versus diagonal direction (bottom) situations.